Renal and Urinary Manifestations of Inflammatory Bowel Disease - Ye Na Kim (The Korean Journal of Gastroenterology, 2019)
The incidence of inflammatory bowel disease (IBD) is increasing rapidly and extra-intestinal manifestations in IBD are also increasing. The prevalence of renal and urinary involvement in IBD ranges from 4-23%. Nephrolithiasis is the most common urinary complication in IBD patients. Parenchymal renal disease is rare but has been well documented and presents most commonly as glomerulonephritis or tubulointerstitial nephritis. The overall morbidity of IBD-related renal manifestations is significant. Therefore, a high index of clinical suspicion and optimal monitoring of the renal function are needed for the early diagnosis and prevention of IBD-related renal manifestations and complications.